Analysis of Fly Ash and Sandblasting Waste Addition in Cementitious Composite Lawn Table Reinforced by Cocofiber and Wiremesh - Widya Emilia Primaningtyas; Inshiro Auliyasari; Wiwik Dwi Pratiwi; Adristi Nisazarifa; Desrilia Nursyifaulkhair; Amanda Rosalina (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Concrete technology has significantly advanced and remains an interesting research topic. The demand for cement usage rises significantly due to concrete usage in various sectors. Cement production leads to air pollution issues and causes a greenhouse effect, even in the modern filtration era. Fly ash is an industrial waste that has been identified as a viable substitute for cement due to its pozzolanic properties. Silica Sand is sandblasting waste, where added value is needed. This study investigates the effectiveness of fly ash substitution in the cement portion of cementitious composite materials as an effort to minimize cement usage. Using sandblasting waste is an effort to implement 3R activity (reduce, reuse, recycle) for maritime waste. Compressive and tensile tests were evaluated in the variation of fly ash substitution for cementitious composite reinforced by coco fiber and wiremesh model. The results show that a 40% fly ash substitution gives the highest compressive strength of 32.98 MPa and the tensile strength of 5.90 N/mm². The best model composition provides the increments of compressive and tensile strength compared to the control specimen at 43.60% and 12.60%, respectively. ANOVA tests confirmed the significance of the enhancing effect as the presence of fly ash, both for compressive and tensile strength. Additionally, static analysis simulations using Fusion360 software were performed and indicated that the cementitious composite lawn table prototype’s design is safe and has good formability, as a safety factor performed 2.26, exceeding the required value of 2.00. This result explicates that fly ash and waste materials can be effectively used in cementitious composites for practical applications.